Researching the vulnerable a guide to sensitive research methods - Liamputtong, Pranee, 1955- (London : SAGE, 2007)
Exploring the considerations and sensitivities of being a researcher faced with a subject group at the margins of society this text explores the ethical, practical and methodological implications of working with such groups.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Marginality, Social -- Research; Social groups -- Research